FCSIT's smart lab and tutorial room booking system with simple bidding mechanism - Ng, Kai Ming (Universiti Malaysia Sarawak (UNIMAS), 2014)
FCSJT's Smart Lab & Tutorial Room Booking System with a Simple Bidding Mechanism is an automated system that help the lab manager to allocate the time slot of the lab and tutorial room. Lecturer send the request into the system and then the system will decide who will get the time slot requested. Lab manager just monitor the system and generate the result. In the current system, the lab manager need to do all of this by human resource. The technology in the current system is just the email system that help lab manager to gather the request. Current system is very time consuming, lab manager need to go through all the request by it owns and decide the time slot.for the request or reject it. Human resources always has it limit and constraints, lab manager may miss out some request or do the decision that not desired by the lecturer. Thus the automated system will overcome this by implement the simple rule base to determine the priority of each request. With the priority generate, it is easy to arrange the time slot. So the automated system will do all of this in just a single click by the lab manager or admin.